FLUKTUASI HARGA CABAI MERAH DI MASA PANDEMI COVID 19 DI KOTA JAMBI - Siti Abir Wulandari (Jurnal MeA (Media Agribisnis), 2020)
The Covid-19 pandemic has stopped community activities. Since last March, various aspects of life in this country have been suspended animation to remote areas including Jambi Province. The stretching routine that fades during the corona pandemic has slowed down the economy. In Jambi, the indicator for the decline in the economic graph can be seen from the shift in the value of inflation / deflation, which reflects movements in the prices of goods / services on the market. A horticultural commodity that is widely developed and is one of the people's needs is red chili. This has resulted in the level of demand for red chili that continues to occur, and at certain times the price of red chili has increased, for example in the new year or during the Eid al-Fitr. This study aims to see the development of the price of large red chilies and curly red chilies and to analyze the differences in price fluctuations of large red chilies and curly red chilies in the city of Jambi. This research was carried out during the Covid 19 pandemic. The study focused on the description of the price of large and curly red chilies in the Angso Duo market, the Talang Banjar market and the Simpang Pulai market. The data collected is a time series in the form of data on the price development of chilies from January to June 2020. The data collected is secondary data in this study, obtained from literature and related agencies, namely the Department of Industry and Trade, Market Service, Central Agency Statistics. In this study using a desk study data collection method. The results showed that in general at the beginning of 2020 there was a difference in the price of curly red chilies in Jambi City from Rp. 40,467, - / kg and there was a decrease to Rp. 15,647, - / kg in June with a decrease of about 61%. This price reduction also applies to large red chilies, which decreased by 55% from Rp. 30,500, - / kg in January to Rp. 13. 647, - / kg in June. The coefficient of variance of large red chilies is 0.38 while curly red chilies are 0.40. The coefficient of variance in plain view shows a difference where the coefficient of variance of the price of curly red chilies is higher than the coefficient of variance of the price of large red chilies. but statistically these two variance coefficients do not show a significant difference.